Can T1W and T2W Dixon Sequences Replace the Standard MRI Protocol in Diagnosing Sacroiliitis? - Nur Betül Karatoprak; Zeynep Maraş Özdemir; Sinan Karatoprak; Ayşegül Sağır Kahraman; Leyla Karaca; Servet Yolbaş (Journal of the Belgian Society of Radiology)
Objectives: This study aims to assess the performances of T1-weighted (T1W) and T2-weighted (T2W) Dixon sequences as replacements for the standard magnetic resonance imaging (MRI) protocol for diagnosing active and chronic sacroiliitis. Materials/Methods: This single-centre, prospective study included 107 patients who underwent 3 Tesla MRIs. The patients with inflammatory low-back pain (aged 18–50 years) were included. The exclusion criteria included pregnancy, pelvic infection/malignancy history, pelvic metal implants or foreign body artefacts. The imaging protocol comprised standard T1W and T2W fat-saturated (T2W-FS) sequences and T1W–T2W Dixon sequences. Active sacroiliitis signs were assessed by comparing T2W-FS images with T2W Dixon water-only (WO) images. Chronic sacroiliitis signs were evaluated by comparing the standard T1W sequence with T1W–T2W Dixon fat-only (FO), in-phase (IP) and out-of-phase (OP) images. The quantitative analysis involved calculating signal-to-noise ratios (SNRs) and contrast-to-noise ratios (CNRs) for bone marrow edema (BME) and periarticular fat deposition (PFD). Descriptive statistics, correlation, diagnostic performance tests and interobserver reliability tests were performed in the qualitative analysis. Results: There were no statistically significant differences in BME detection between the T2W-FS and T2W Dixon-WO images. T2W Dixon exhibited significantly greater SNRs–CNRs than did the standard protocol for BME and periarticular fat deposition assessments. T1W–T2W Dixon imaging demonstrated sufficiently high diagnostic performance for detecting erosions, periarticular fat deposition and ankylosis compared with the standard protocol. Conclusions: The T2W Dixon sequence has the potential to replace the standard protocol, which would reduce acquisition time. However, we do not recommend the use of the T1W Dixon sequence in routine practice, since standard T1W images provide similar or superior results to T1W Dixon images.